Incidence of Nausea and Vomiting After Fast-Track Anaesthesia for Heart Surgery - Hijazi,Emad Mohamed (2018)
Abstract Objective: The aim of this study was to evaluate the incidence of postoperative nausea and vomiting (PONV) after fast-track cardiac anesthesia (FTCA) in the first 24-48 hours in the cardiac intensive care unit (CICU) after open-heart surgery, risk factors for PONV and its influence on CICU length of stay. Methods: A prospective observational study from January 1, 2013 to the end of December 2015 was performed in the CICU of a university hospital in the north of Jordan and Queen Alia Heart Institute, Amman, Jordan. Three hundred consecutive patients undergoing fast-track cardiac anesthesia in elective cardiac surgery were enrolled in the study. Nausea and vomiting were assessed after tracheal extubation, which was performed within 6-10 hours after surgery and during the first 24-48 hours in the CICU. Metoclopramide 10 mg intravenously was used as the initial antiemetic drug, but ondansetron 4 mg intravenously was also used as second line of management. Results: Nausea was reported in 46 (15.3%) patients, and vomiting in 31 (10.3%). Among females, 38 (33.9%) patients developed nausea and 20 (17.9%) developed vomiting. Among males, 8 (4.3%) patients developed nausea and 11 (5.9%) developed vomiting. Conclusion: PONV are relatively low after FTCA and the prophylactic administration of antiemetic drug before anesthesia or after extubation is not necessary.